Why the American Academy of Pediatrics recommends initiating HPV vaccine at age 9 - Sean T. O'Leary (Taylor & Francis Group, 2022)
The American Academy of Pediatrics (AAP) recommends starting the human papillomavirus (HPV) vaccine series between 9 and 12 years, at an age that the provider deems optimal for acceptance and completion of the vaccination series. This recommendation differs from the Advisory Committee on Immunization Practices (ACIP), which recommends HPV vaccination be initiated at age 11 or 12 years, stating the series can be started at age 9 years. This commentary discusses the reasoning behind AAP's decision to differ from ACIP, as the AAP and ACIP schedules are essentially harmonized for all other vaccines. Reasons include recognition that (1) vaccination uptake is suboptimal; (2) offering vaccination earlier offers provider's flexibility in introducing the vaccine; (3) initiating the vaccine at age 9 or 10 may be preferable for parents or adolescents who do not want to receive ≥3 concomitant vaccines at age 11 or 12; (4) earlier initiation may disentangle HPV recommendations from discussions of sexuality; (5) earlier recommendation might alleviate HPV vaccine hesitancy "fatigue;" (6) the immune response is robust at younger ages with no evidence of waning protection; and (7) there is a dearth of evidence supporting starting the recommendation at age 11 or 12 within the "adolescent immunization platform."